2006
DOI: 10.1111/j.1365-3083.2006.01857.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of IgG Antibody Against Measles, Mumps and Rubella in Bangladeshi Children: A Pilot Study to Evaluate the Need for Integrated Vaccination Strategy

Abstract: The present study was carried out to determine the seroprevalence of IgG antibodies in Bangladeshi children against measles (irrespective of vaccination status), mumps and rubella (MMR) to assess strategic need of combined vaccination for these diseases. A total of 456 children of 1 month to 15 years, were studied. Serum IgG antibodies against MMR were measured by enzyme‐linked immunosorbent assay (ELISA). By 3 months, protective IgG antibody level (>40 AU for measles and mumps and >15 IU/ml for rubella) for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
6
10
0
Order By: Relevance
“…All countries surveyed, having a developed or developing status, had national vaccination programmes. However, of the countries in the least developed status, two of the 13 countries (Guinea-Bissau and Bangladesh) [10,25,70,77,89] reporting measles serosurveys and six of the eight countries (Bangladesh, Burkina Faso, Nepal, Nigeria, Sudan and Tanzania) [25,54,56,81,85,97,98] reporting rubella serosurveys reported having no nationally coordinated vaccination programme at the time of the study. Forty-three percent of published measles serosurveys were conducted in developed countries, reflecting the need to identify susceptible populations and immunization gaps as these countries move towards achieving the measles elimination goal.…”
Section: Countries In Which Studies Were Conductedmentioning
confidence: 96%
See 4 more Smart Citations
“…All countries surveyed, having a developed or developing status, had national vaccination programmes. However, of the countries in the least developed status, two of the 13 countries (Guinea-Bissau and Bangladesh) [10,25,70,77,89] reporting measles serosurveys and six of the eight countries (Bangladesh, Burkina Faso, Nepal, Nigeria, Sudan and Tanzania) [25,54,56,81,85,97,98] reporting rubella serosurveys reported having no nationally coordinated vaccination programme at the time of the study. Forty-three percent of published measles serosurveys were conducted in developed countries, reflecting the need to identify susceptible populations and immunization gaps as these countries move towards achieving the measles elimination goal.…”
Section: Countries In Which Studies Were Conductedmentioning
confidence: 96%
“…Several authors demonstrated that vaccinated individuals have lower GMT compared with those acquiring immunity through natural infection [9,10,[15][16][17]19,[24][25][26]30,34,69,96,99]. There was insufficient information provided to determine if certain vaccination programmes resulted in a lower GMT.…”
Section: Major Findings Of the Reviewmentioning
confidence: 98%
See 3 more Smart Citations